Effect of Stone Density, Skin-Stone Distance and Stone Size on Extracorporeal Shock Wave Lithotripsy Success of Ureter Stones: A Clinical Investigation - Erhan Erdoğan; Fatih Özçelik; Gül Kahraman; Mihriban Şimsek; Kemal Sarıca (The New Journal of Urology)
Objective: This study aimed to investigate the correlation between demographic characteristics, stone size, density, and location, skin-to-stone distance (SSD), urinary parameters, and the success rate of extracorporeal shock wave lithotripsy (ESWL) in patients with ureteral stones. Material and Methods: A total of 151 patients with ureteral stones were included in this retrospective study, and ESWL treatment was successful in 116 of them. Stone size, density, and ureteral location (upper/lower and right/left) were evaluated using non-contrast computed tomography, and SSD was measured. Demographic characteristics [age, gender, and BMI (Body Mass Index)] and complete urinalysis parameters (pH, specific gravity, protein, leukocytes, erythrocytes, casts, and various crystal types) were recorded. The impact of these factors on ESWL success was statistically analyzed. Results: A significant negative correlation was found between ESWL success and stone density [in Hounsfield units (HU)], SSD, and patient age. Treatment success was lower for hard stones (HU ≥ 1000) compared to soft stones (HU < 1000) (ESWL successful: 28/45 (62%) vs 88/106 (83%), p = 0.006). Similarly, patients with successful ESWL had lower ages and SSD compared to those with unsuccessful outcomes (41±13 vs 45±9 years and 117±18 vs 125±17 mm, respectively). Additionally, stones with higher density were found to be larger compared to those with lower density, with a low-level positive correlation (9.0(4.8-15.0) vs 7.8(4.2-15.0) mm, p=0.0458; r=0.240, p=0.0029). Binary regression analysis revealed that SSD, stone density (HU), and stone location significantly influenced ESWL success and could predict outcomes with 78.8% accuracy (p=0.005, 0.002, and 0.014, respectively). Conclusion: Increased stone density, longer SSD, and advanced age can decrease the success of ESWL treatment. This study highlights the importance of considering these variables when planning ESWL treatment.